Virtual learning environments as mediation in the accompanying of the curriculum stage in the distance mode (Research, Society and Development, 2016)
This paper aims to present conceptual characteristics of virtual learning environments and their contributions to the mediation and monitoring of the Supervised Curricular Internship within the distance modality. In order to do so, through a bibliographic review, it was verified that virtual learning environments are considered important locus in the EAD mediation, so that it harmonizes the interaction between the subjects involved in the process and in the interactivity with the available resources, adding flexibility Of time, autonomy, breaking geographical limitations. As a consequence, the use of virtual environments in the monitoring of Supervised Internship is an open field of possibilities and can bring several benefits for students and tutors and to mediate this relationship. Such potentialities are not generated without the counterpart of challenges to be overcome to be realized, especially the adequate preparation of tutors for the correct and effective use of the available applications.